Seasonality of tuberculosis among suspect patients visiting National Medical College, Teaching Hospital, Birgunj, Nepal - Shidiki, A; Pandit, BR; Bhargava, D; Mondal, S; Rijal, BP (Journal of Institute of Medicine Nepal, 2014)
Introduction: Seasonal variations of tuberculosis have been demonstrated in a number of studies with reported peaks in late winter and early spring or summer. The study was to analyze effect of seasonal variation on tuberculosis suspects across the calendar year.Methods: The research work was conducted in National Medical College & Teaching Hospital from January to December 2012. The sputum samples were collected and processed for acid fast bacilli from suspected tuberculosis patients.Results: Among 1403 suspected tuberculosis patients, 57.0% were male and 43.0% were females. 11.3% male and 4.0% female were present among the suspected cases of tuberculosis. The highest number of cases was in the age group 51-60.There was no any significant difference in between positive cases and age group (P=0.637). The positive cases of tuberculosis were found in 8.7% Muslim and 8.1% Hindu significant difference was not found in religion and tuberculosis (P=0.780%). The highest cases of tuberculosis was detected in June (14.9%) and to decline from august (13.2%) through December (4.4%). There was significant relation for cases and month (P=0.00001). More severe (3+) cases were found more (10.6%) in June, 2+ (4.4%) in July and 1+ (9.7%) in August which was statistically significant (P=0.00001).Conclusion: The seasonal variability of tuberculosis case detection showing mostly a peak in numbers in early spring and summer months.